Daily Low-Dose Cisplatin-Based Concurrent Chemoradiotherapy for the Treatment of Cervical Cancer in Patients 70 Years or Older. Issue 5 (June 2015) - Hanawa, Shinsuke; Mitsuhashi, Akira; Usui, Hirokazu; Yamamoto, Noriko; Watanabe-Nemoto, Miho; Nishikimi, Kyoko; Uehara, Takashi; Tate, Shinichi; Uno, Takashi; Shozu, Makio
Abstract : Objectives: It has been established that concurrent chemoradiotherapy (CCRT) is efficacious for cervical cancer, but adherence is unsatisfactory among elderly patients. To improve adherence, we have developed and initiated a daily low-dose cisplatin-based CCRT regimen. Here, we retrospectively evaluated the use of CCRT, especially for elderly patients. Methods: The study included a total of 53 patients who were 70 years or older, had stage IB-IVA cervical cancer, and were initially treated with daily CCRT. The daily CCRT comprised pelvic external beam radiotherapy (2 Gy/d × 25) with daily low-dose cisplatin (8.0 mg/m 2 per day) and either low- or high-dose-rate intracavitary brachytherapy. Results: The median age was 72 years (range, 70–85 years). The median follow-up duration was 32 months (range, 2–104 months). The 3-year overall survival rate was 79.0%. Daily cisplatin chemotherapy was successfully completed in 32 (60.4%) of the 53 patients. Grade 3 or 4 neutropenia was observed in 19 patients (36%). A late complication of grade 3 rectal hemorrhage occurred in 3 patients who received high-dose-rate brachytherapy. All primary tumors responded to daily CCRT; complete response was observed in 43 patients (91.5%) and partial response was observed in 4 patients (8.5%). Conclusions: Daily CCRT in patients 70 years and older had acceptable compliance and safety. Daily CCRT is suggested to be a good treatment option for elderly patients who have advanced cervical cancer and require concurrent cisplatin.